A gain‐of‐function mutation of plastidic invertase alters nuclear gene expression with sucrose treatment partially via GENOMES UNCOUPLED1‐mediated signaling. Issue 3 (27th January 2015) - Maruta, Takanori; Miyazaki, Nozomi; Nosaka, Ryota; Tanaka, Hiroyuki; Padilla‐Chacon, Daniel; Otori, Kumi; Kimura, Ayako; Tanabe, Noriaki; Yoshimura, Kazuya; Tamoi, Masahiro; Shigeoka, Shigeru
Summary Plastid gene expression (PGE) is one of the signals that regulate the expression of photosynthesis‐associated nuclear genes (PhANGs) via GENOMES UNCOUPLED1 (GUN1)‐dependent retrograde signaling. We recently isolated Arabidopsis sugar‐inducible cotyledon yellow‐192 (sicy‐192), a gain‐of‐function mutant of plastidic invertase, and showed that following the treatment of this mutant with sucrose, the expression of PhANGs as well as PGE decreased, suggesting that the sicy‐192 mutation activates a PGE‐evoked and GUN1‐mediated retrograde pathway. To clarify the relationship between the sicy‐192 mutation, PGE, and GUN1‐mediated pathway, plastid and nuclear gene expression in a double mutant of sicy‐192 and gun1‐101, a null mutant of GUN1 was studied. Plastid‐encoded RNA polymerase (PEP)‐dependent PGE was markedly suppressed in the sicy‐192 mutant by the sucrose treatment, but the suppression as well as cotyledon yellow phenotype was not mitigated by GUN1 disruption. Microarray analysis revealed that the altered expression of nuclear genes such as PhANG in the sucrose‐treated sicy‐192 mutant was largely dependent on GUN1. The present findings demonstrated that the sicy‐192 mutation alters nuclear gene expression with sucrose treatment via GUN1, which is possibly followed by inhibiting PEP‐dependent PGE, providing a new insight into the role of plastid sugar metabolism in nuclear gene expression.